Creating human rights : how noncitizens made sex persecution matter to the world - Alfredson, Lisa S. (Pennsylvania studies in human rights., 2009)
Selected by Choice magazine as an Outstanding Academic Title Creating Human Rights offers the first systematic study of a pioneering women's refugee movement and its challenge, as an international trigger case, to more conventional paths toward human rights policy development. Lisa S. Alfredson argues that such cases, which unfold in the context of a specific country and have profound impacts on international human rights efforts, have been neglected in research and pose a challenge to recent theorizing on human rights change. In the early 1990's, Canada witnessed the emergence of the world's first comprehensive refugee policy for women who were seeking protection from female-specific forms of violence-rape, domestic abuse, public stoning of adulterers, genital mutilation-while challenging a gender-biased system. Close examination of this novel movement, Alfredson contends, provides crucial insights into why and how states may articulate new human rights that set international precedents. Analyzing original empirical data and sociopolitical historical trends, the book documents the decisive global impacts of the movement while shedding light on the paradox of noncitizen politics and asylum seekers' little recognized political strength. Contrary to expectation, findings suggest transnational networks and pressures are not required for some forms of change. Rather, international trigger cases illuminate a range of other key actors and advocacy strategies leading, subsequently, to a more comprehensive understanding of human rights acceptance.In the case of the women's refugee movement, the convergence of human rights and noncitizen politics points toward a new dimension for human rights scholarship that, in the current age of globalization, is becoming critically important.